Why did the Big Four get so large? Evidence from Australia - Ferguson, Colin; Pinnuck, Matthew; Skinner, Douglas J. (Review of Accounting Studies, 2025)
We use a long time-series from Australia to shed light on economic factors that led to audit market concentration and the Big N. We show that increases in the size of a small number of public companies was an important factor that led to large audit firms and market concentration. We also show that emerging Big N firms made sunk cost investments, including in the ability to provide industry expertise and non-audit services, which allowed them to retain clients, differentiate, and grow. These changes occurred around the time the profession lifted restrictions on advertising, which helped facilitate differentiation, and that larger, more complex clients switched to emerging Big N firms while smaller clients switched to non-Big N firms. We do not find that increases in audit market concentration reduced competition; our results instead suggest the audit market became more competitive over time.